The Moderating Effect of Gender Diversity on the ESG and Financial Performance: Evidence from Indonesia - Rahmi Syafitri; Noorlailie Soewarno (Universitas Pendidikan Ganesha, 2025)
This study examines whether board diversity moderates the impact of ESG on firm performance. The method used in this study is a quantitative approach using moderation regression analysis (MRA). This study uses databases from Bloomberg and Osiris to analyze the impact of ESG practices and gender diversity on firm performance. The sample of this study was 89 public companies in Indonesia during 2015-2023. The results show that ESG practices have a significant positive impact on company performance, increasing stakeholder trust and contributing to sustainable growth. Companies with high ESG scores are also more resilient in facing environmental and social risks. This study also found that gender diversity on the board of directors strengthens the relationship between ESG and company performance. Female representation on the board of directors can improve decision-making dynamics, encourage innovation, and enhance compliance with stricter sustainability standards. Therefore, companies with better gender diversity on their boards of directors are more likely to achieve optimal performance through more effective implementation of ESG policies. This research offers novelty by demonstrating that gender diversity on boards acts as a reinforcing mechanism that enhances the effectiveness of ESG practices on firm performance. This study differs from previous literature by integrating ESG and gender diversity into a single analytical framework to explain firm value creation and sustainability.